PERSONAL QUALITIES OF SECONDARY SCHOOL STUDENTS WITH CRITICAL THINKING - Belousova, A. K. (Modern Psychology, 2019)
The article provides an overview of modern ideas about critical thinking. Based on the analysis of research, the author reveals the features of critical thinking characteristic of high school students, identifies the psychological determinants of the development of critical thinking. The author formulates his own position, which is based on the idea of the dominance of the selection function in the processes of thinking of people with dominant critical thinking. The function of selection, according to the author, is to assess, select, screen out and verify information received by a person. The author formulates the hypothesis of the study, according to which high school students have a certain set of psychological factors and features of the motivation to achieve success, which are associated with critical thinking. The results of an empirical study of critical thinking of high school students, which demonstrate the relationship of factors E, M, H, Q4 with critical thinking, are presented.
Keywords: critical thinking, psychological determinants, reflexivity, adolescence, appraisal activity, independent thinking.